Emotional intelligence and holistic student development: an assessment of psychological and social efficacy in vocational university English education - Xuan, Qilin (Frontiers in Psychology, 2025)
The role of Emotional Intelligence (EI) in university English education has garnered increasing attention, particularly regarding its impact on students’ psychological well-being and social competencies. This study explores how EI influences university students’ psychological adaptability, interpersonal communication skills, and overall learning experience. Employing a mixed-methods approach, this research integrates quantitative surveys and qualitative in-depth interviews to assess the EI levels and their psychological and social efficacy among university English learners at Jiujiang Polytechnic University of Science and Technology. Data analysis reveals a significant correlation between higher EI levels and better mental health, enhanced social interaction skills, and a more positive learning attitude. Through the integration of EI training within university English courses, students exhibit improved self-regulation and teamwork abilities. Furthermore, this study underscores the necessity of incorporating EI into university English teaching and provides both theoretical foundations and practical recommendations for future curriculum design and pedagogical strategies. The findings offer valuable insights for English educators, mental health professionals, and educational policymakers.